Efektifitas Knee Pain Exercise Dan Kompres Hangat Terhadap Nyeri Osteoarthritis Lutut Di Desa Mojolegi Kecamatan Gading Kabupaten Probolingg0 - Era Sasmita; Ainul Yaqin Salam; Grido Handoko Sriyono (Pusat riset dan Inovasi Nasional, 2023)
Osteoarthritis of the knee in the elderly can cause pain due to the degradation of joint cartilage in which the joint cartilage is damaged which is characterized by changes in the joint capsule and damage to the cartilage located at the bone joints. Knee Pain Exercise and warm compresses are two methods that can be used to manage knee osteoarthritis pain.. The purpose of this study was to analyze the effectiveness of knee pain exercise and warm compresses on reducing knee osteoarthritis pain in the elderly. Using a purposive sampling technique, a sample of 40 respondents was drawn from the population of up to 125 people. A cross-over group design technique and a quasi-experimental approach were used in the research design. The instrument used was a Numeric Rating Scale (NRS) observation sheet. The normality of the data was tested using the Kolmogorov-Smirnov. The hypotheses were tested and analyzed using paired samples T test with p-value 0.000 on each variable which means that there is an effect of knee pain exercise and warm compresses on knee osteoarthritis pain. The effectiveness test used independent samples test and it was found that warm compresses had the smallest mean value (2.55), which means that warm compresses were more effective in reducing knee osteoarthritis pain than knee pain exercise. It is expected that the elderly who experience knee osteoarthritis pain do regular exercise which is a physical exercise to reduce knee osteoarthritis pain.